The Innate Immune System and Cardiovascular Disease in ESKD: Monocytes and Natural Killer Cells - Dounousi, Evangelia; Duni, Anila; Naka, Katerina K.; Vartholomatos, Georgios; Zoccali, Carmine (Current Vascular Pharmacology, 2021)
Adverse innate immune responses have been implicated in several disease processes, including cardiovascular disease (CVD) and chronic kidney disease (CKD). The monocyte subsets natural killer (NK) cells and natural killer T (NKT) cells are involved in innate immunity. Monocytes subsets are key in atherogenesis and the inflammatory cascade occurring in heart failure. Upregulated activity and counts of proinflammatory CD16+ monocyte subsets are associated with clinical indices of atherosclerosis, heart failure syndromes and CKD. Advanced CKD is a complex state of persistent systemic inflammation characterized by elevated expression of proinflammatory and pro-atherogenic CD14++CD16+ monocytes, which are associated with cardiovascular events and death both in the general population and among patients with CKD. Diminished NK cells and NKT cells counts and aberrant activity are observed in both coronary artery disease and end-stage kidney disease. However, evidence of the roles of NK cells and NKT cells in atherogenesis in advanced CKD is circumstantial and remains to be clarified. This review describes the available evidence regarding the roles of specific immune cell subsets in the pathogenesis of CVD in patients with CKD. Future research is expected to further uncover the links between CKD associated innate immune system dysregulation and accelerated CVD and will ideally be translated into therapeutic targets.
Keywords: heart failure